Pelatihan Pemrograman Bahasa C++ SMK Ibrahimy 1 Sukorejo - Anang Maulana Zulfa; Wafi Riga Ramadhani; Zaehol Fatah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The C++ training program held at SMK Ibrahimy 1 Sukorejo aims to improve students' skills in creating software using the C++ language. This activity is designed to provide a basic, intermediate-level understanding of C++ syntax, data structures, algorithms, and applications in simple programming. Participants in this training were 10th and 11th grade students majoring in Computer and Network Engineering (TKJ) and Software Engineering (RPL), taught by experienced instructors in the field of programming. The training approach consisted of interactive lectures, demonstrations, hands-on practice, and small projects aimed at honing students' problem-solving skills. The material covered included an introduction to variables, data types, operators, branching, looping, functions, arrays, and the fundamentals of object-oriented programming (OOP). Furthermore, participants were introduced to the use of Integrated Development Environments (IDEs) such as Code::Blocks and Visual Studio Code to assist with coding and debugging. Evaluation results showed a significant increase in students' knowledge of C++ programming concepts, with 85% of them successfully creating functional programs based on the assigned modules. This training also fosters collaboration among students through group discussions and peer assessments, thus fostering teamwork skills. It is hoped that this activity will serve as a starting point for students to develop further programming projects and prepare them for competition or the world of work in the information technology sector.